Molecular dynamics and functional studies define a hot spot of crystal contacts essential for PcTx1 inhibition of acid-sensing ion channel 1a - Saez, N.; Deplazes, Evelyne; Cristofori-Armstrong, B.; Chassagnon, I.; Lin, X.; Mobli, M.; Mark, A.; Rash, L.; King, G. (John Wiley & Sons, 2015)
Background and Purpose: The spider-venom peptide PcTx1 is the most potent and selective inhibitor of acid-sensing ion channel (ASIC) 1a. It has centrally acting analgesic activity and is neuroprotective in rodent models of ischaemic stroke. Understanding the molecular details of the PcTx1: ASIC1a interaction should facilitate development of therapeutically useful ASIC1a modulators. Previously, we showed that several key pharmacophore residues of PcTx1 reside in a dynamic ß-hairpin loop; conclusions confirmed by recent crystal structures of the complex formed between PcTx1 and chicken ASIC1 (cASIC1). Numerous peptide: channel contacts were observed in these crystal structures, but it remains unclear which of these are functionally important. Experimental Approach: We combined molecular dynamics (MD) simulations of the PcTx1: cASIC1 complex with mutagenesis of PcTx1 and rat ASIC1a. Key Results: Crystal structures of the PcTx1: cASIC1 complex indicated that 15 PcTx1 residues form a total of 57 pairwise intermolecular contacts (<Å) with 32 channel residues. MD simulations, however, suggested that about half of these interactions do not persist in solution. Mutation to alanine of only eight of 15 PcTx1 contact residues substantially altered ASIC1a inhibition by PcTx1. Our data reveal that many of the peptide-channel interactions observed in the PcTx1: cASIC1 crystal structures are not important for PcTx1 inhibition of rat ASIC1a. Conclusions and Implications We identified the atomic interactions that are critical for PcTx1 inhibition of ASIC1a. Our data highlight the value of combining structural information, MD and functional experiments to obtain detailed insight into the molecular basis of protein: protein interactions.